Influence research of profile chords ratio on aerodynamic characteristics of tandem compressor cascade - Терещенко, Юрий Матвеевич; Дорошенко, Екатерина Викторовна; Аболхассан, заде Джалал (Eastern-European Journal of Enterprise Technologies, 2015)
Efficiency improvement of gas turbine compressors is ensured by the extensive use of tandem blade rows in straightener blades of the last stages of multistage axial compressors. Their installation provides large flow deflection angles in the unstalled flow of blade rows and, consequently, a low level of losses in the design mode of the compressor. The problem of influence research of the first- and second-row blade chords ratio in tandem blade rows in a wide range of angles of attack is relevant and is of practical interest in developing recommendations for ensuring the gas-dynamic stability of gas turbine compressors. To solve the problem, the method of the computational experiment was used and characteristics of tandem compressor cascade with different first- and second-row blade chords ratios were calculated in the paper. The calculation results of the characteristics of tandem cascade were compared with the characteristics of an equivalent single compressor cascade. For the computational domain of the studied tandem and equivalent single cascades, small adaptive unstructured grid and the second-order design scheme with the local use of the first-order design scheme (High resolution) was applied. The Menter's SST model was used to solve the problems. The results showed that the aerodynamic characteristics of the tandem compressor cascades essentially depend on the first- and second-row blade chords ratio. With positive angles of attack, the quality parameter of tandem cascades is higher than that of single, with the first- and second-row blade chords ratio, corresponding to the position of the slot xщ=(0,3 ... 0,4)b∑. With negative angles of attack, the quality parameter of tandem cascades is higher than that of single, with the first- and second-row blade chords ratio, corresponding to the position of the slot xщ=(0,5 ... 0,7)b∑.